Research on education and employment in Vietnam in 2010 " Empirical research in the Red River Delta and the Northwest area - Vuong, Thuy Anh (2020)
It is often assumed that education Is a passport to good jobs. People who spend more time for improve their education level may have good jobs with higher income. Also, people in Vietnam have a trend of paying much money for education because it is widely believed that investment for education can yield highest interest. These conceptions provoke the author to find and examine evidences in order to clarify relationship between years of schooling and job opportunity, years of schooling and income and the link between income and educational expenditure.